Implementation of Tin Mining Mineral and Coal Policy in the Bangka Belitung Islands - Alzena Rhianazala; Abdul Nadjib (Universitas PGRI Madiun, 2025)
This study aims to analyze the implementation of tin and coal mining policies in the Bangka Belitung Islands. It uses a qualitative analysis approach and focuses on unconventional tin mining in the Bangka Belitung Islands. This study employs the implementation theory framework proposed by Donald Van Metter and Carl Van Horn, which includes policy objectives, resources, characteristics of implementing agents, implementers' dispositions, interorganizational relationships, and social, political, and economic conditions. Data were collected through literature review using administrative law to determine standards and their application. The findings of this study indicate that there are still numerous illegal tin mines, which cause losses for the local community and the Bangka Belitung region.